Land Optimization to Improve the Economy through Attractive Tourist Destinations in Smart City Indonesia - Asfahani Asfahani; Tono Mahmudin; Zohaib Hassan Sain (Edujavare Publishing, 2023)
Increasing urbanization and technological developments have triggered significant transformations in urban land management, especially in Indonesia's Smart City. This study aims to formulate and implement land optimization strategies by developing attractive tourist destinations in Smart City, Indonesia. This community service research method uses the ABCD (Asset Based Community Development) method, which prioritizes valuable aspects owned by a community, better known as an asset-based approach, with five stages: Discovery, Dream, Planning, Define, and Destiny. The results provide a comprehensive view to support the development of tourist destinations responsive to smart cities in Indonesia, marking an important contribution to sustainable and innovative city development. So, it is concluded that developing smart and sustainable tourist destinations is crucial in maximizing land use in Indonesia's Smart Cities. The integration of smart technology, community participation, and environmental sustainability are key elements in creating tourist destinations that are not only attractive but also contribute to local economic growth and environmental preservation.